DAMPAK LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN DENGAN NIAT SEBAGAI VARIABEL MEDIASI - Sukma Irdiana; Kurniawan Yunus Ariyono; Kusnanto Darmawan (Jurnal Ilmiah Global Education, 2023)
This study aims to examine and analyze the impact of Financial Literacy and Financial Attitudes on Financial Management Behavior with Intentions as Intervening Variables. This research is quantitative research with data collection techniques using a questionnaire. The sample is 140 respondents. The sampling technique used is purposive sampling with predetermined criteria, namely people who earn at least IDR 3,000,000 per month. Processing primary data using statistical analysis techniques Package for Social Science (SPSS) with multiple regression analysis methods, path analysis and sobel test. The results of this study indicate that financial literacy has a negative but not significant effect on intentions, while financial attitudes have a positive and significant effect on intentions. Furthermore, financial literacy and intention have a positive but not significant effect on financial management behavior, while financial attitudes have a positive and significant effect on financial management behavior. In addition, the results of the study show that intention is not able to mediate financial literacy on financial management behavior but intention is able to mediate financial attitudes on community financial management behavior with a significant influence.